The last passage : recovering a death of our own - Heinz, Donald (Oxford University Press, 1999)
The author calls for the reinvestment of dying with the rituals that once gave it spiritual and social meaning, surveying the many ways death has been treated throughout history and demonstrating how the arts might lend a renewed reverence to death.